Trends and Determinants of Skilled Birth Attendants' use among Women of Reproductive Age in Tanzania: Evidence from the 2004/05–2022 Demographic Health Surveys - Jovin R. Tibenderana; Sanun Ally Kessy; Victoria Godfrey Majengo; Erick Donard Oguma; Tegemea Patrick Mwalingo; Mussa Hassan Bago; Immaculata P. Kessy; Elihuruma Eliufoo Stephano; Azan Abubakar Nyundo; Mtoro J. Mtoro (PLoS ONE, 2025)
Background Skilled birth attendants (SBAs) are vital for reducing maternal and newborn morbidity and mortality, yet their use remains below national and global targets, particularly in low and middle-income countries like Tanzania. This study aimed to assess trends and determinants of SBA use among women of reproductive age (WRA) in Tanzania. Methods This was an analytical cross-sectional study among WRA in Tanzania, using data from the Demographic and Health Surveys (DHS) 2004/05, 2010, 2015/16, and 2022. Data analysis was performed using STATA version 18. Analysis considered the complex survey design through the application of weights, clustering, and strata. Modified Poisson regression models estimated the determinants associated with SBA use among WRA. Results were presented using adjusted prevalence ratio (APR) with a 95% confidence interval. Results The study found an increased proportion of SBA use among WRA trends from 57.24% (2004/05) to 84.76% (2022), with the Dar es Salaam region showing higher SBA use of 86.6% in 2022. Residing in rural (APR = 0.96, 95% CI: 0.94, 0.99), secondary/higher education (APR = 1.10, 95%CI: 1.04, 1.15), being rich (APR = 1.07, 95% CI:1.02, 1.13), 2 + birth order (APR = 0.91, 95% CI: 0.88, 0.93), distance to health facility not big problem(APR = 1.08, 95% CI: 1.05, 1.12), ≥ 4 ANC contacts (APR = 1.13, 95% CI: 1.08, 1.17), and partners with secondary/ higher education (APR = 1.15, 95% CI: 1.07, 1.23) were the determinants found significantly associated with SBA use. Conclusion Despite the upward trend, SBA use remains below the 2025 national target.. Interventions should prioritize improving access to maternal services in rural areas, expanding women’s and partners’ education, strengthening ANC uptake, and addressing financial barriers. These strategies are critical to close the coverage gap and ensure equitable skilled care during childbirth.